Comparative proteomic analysis of normal and gliotic PVR retina and contribution of Müller glia to this profile. (December 2018) - Eastlake, Karen; Heywood, Wendy E.; Banerjee, Phillip; Bliss, Emily; Mills, Kevin; Khaw, Peng T.; Charteris, David; Limb, G. Astrid
Abstract: Müller glia are responsible for the neural retina regeneration observed in fish and amphibians throughout life. Despite the presence of these cells in the adult human retina, there is no evidence of regeneration occurring in humans following disease or injury. It may be possible that factors present in the degenerated retina could prevent human Müller glia from proliferating and neurally differentiating within the diseased retina. On this basis, investigations into the proteomic profile of these cells and the abundance of key proteins associated to Müller glia in the gliotic PVR retina, may assist in the identification of factors with the potential to control Müller proliferation and neural differentiation in vivo . Label free mass spectrometry identified 1527 proteins in Müller glial cell preparations, 1631 proteins in normal retina and 1074 in gliotic PVR retina. Compared to normal retina, 28 proteins were upregulated and 196 proteins downregulated by 2-fold or more in the gliotic PVR retina. As determined by comparative proteomic analyses, of the proteins highly upregulated in the gliotic PVR retina, the most highly abundant proteins in Müller cell lysates included vimentin, GFAP, polyubiquitin and HSP90a. The observations that proteins highly upregulated in the gliotic retina constitute major proteins expressed by Müller glia provide the basis for further studies into mechanisms that regulate their production. In addition investigations aimed at controlling the expression of these proteins may aid in the identification of factors that could potentially promote endogenous regeneration of the adult human retina after disease or injury. Highlights: Proteomic analyses showed evidence for Müller glia contribution to retinal gliosis. Polyubiquitin-C and HSP90a produced by Müller glia, are upregulated in gliotic retina. Müller glia are a source of prelamin, elongation factor and serpin found in retina.